2021
DOI: 10.1111/ajco.13639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus comorbidity on outcomes in stages II and III colorectal cancer

Abstract: Aim The effects of diabetes mellitus (DM) on the outcomes of colorectal cancer (CRC) are controversial. This retrospective study evaluated the effects of DM on American Joint Committee on Cancer (AJCC, 7th) Stages II and III CRC patients who received curative surgery. Methods We reviewed the records of CRC patients who were treated from January 2008 to December 2014 and identified the presence of DM and hypertension prior to CRC diagnosis. Cox proportional hazards analyses were used for prognostic factor deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…According to Lin et al 2021 [ 27 ] diabetic patients with CRC have a higher mortality rate than non-diabetic patients, and it is critical to control and manage DM-associated disorders in order to improve survival in patients with CRC patients with T2DM. Furthermore, Mills et al 2013 [ 28 ] found that diabetes was linked with a 17% increased risk of all-cause mortality in CRC patients in a meta-analysis of 21 studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lin et al 2021 [ 27 ] diabetic patients with CRC have a higher mortality rate than non-diabetic patients, and it is critical to control and manage DM-associated disorders in order to improve survival in patients with CRC patients with T2DM. Furthermore, Mills et al 2013 [ 28 ] found that diabetes was linked with a 17% increased risk of all-cause mortality in CRC patients in a meta-analysis of 21 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Huh et al [26] proposed a new histological rating to be used in the follow-up of CRC patients, which considers the presence of LVI. Although many studies have shown that DM is associated with poor prognosis in CRC patients, as in all cancers, its effect on LVI remains a matter of debate [27][28][29]. Little information in the literature provides an idea of how LVI is affected in CRC patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, both hereditary and environmental variables are thought to impact sex and gender disparities. While some studies have found that age and sex have little or no bearing on the risk of death in patients with colorectal cancer [ 43 ], the present study outcome shows gender to be a significant predictor of death (survival) as the male gender has about a three-fold increased risk of dying from colorectal cancer in an at-risk range of 2–9 times (95% CI) than the female patients ( p -value = 0.040). Similar findings have also been reported in several studies [ 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%